(NzAKONODAWSTWO uKRA)QÇNI PRO [L@B TA SÆM(B'(N@ (B/s)E - (NsP)QÆWAK(B, (Nw(B. (Nm(B.,s)E ((NkI)QÇW (B:s)E (NnAUKOWA DUMKA(B,s, 1998)
(Nw P)QÆDRU^NIKU WISWÆTLENO ZAKONODAWSTWO uKRAÇNI Z PITANX [L@BU TA SÆM(B"Çs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NpRAWOs -- (Ns)QÆMEJNE PRAWOs)E; (N[L@Bs; (NS)QÆMEJNE PRAWOs)E; (NUKLADENNQ [L@BUs; (NPODRUVVQs; (NMAJNOW)QÆ PRAWAs)E; (NNED)QÆJSNÆSTX [L@BUs)E; (NBATXK)QÆWSTWOs)E; (NOP)QÆKAs)E; (NUSINOWLENNQs; (NP)QÆKLUWANNQs)E